DETERMINATION OF ACTIVITY HYDROGEOCHEMICAL AND HYDRODYNAMIC OF WATER WELLS UMERDUHUMA AQUIFER SOUTH-WESTERN IRAQ - Abas, Falah (Iraqi Journal of Science, 2024)
Hydrogeochemical analyses were done for UmErduhuma aquifer in S-W Iraq which have got cation and anion concentrations . This study shows the origin of the water is rainfall except well No.2 where is marine . the chemical of the water type of the wells No. 3,4,5,6, and 7 are calisum-sulfate while the wells No. 1 and 2 are sodium- sulfate . They are useful to irrigation jobs but they are not use in a human activity without biological and chemical treatment . The hydrodynamic study shows that the hydrodynamic activity is high so that hydro carbonic accumulation is a little , except well No.(2).